Between Grammar Rules and Meaning in Weighing the Ambiguities of Syntax in Al-Bayḍawi’s Interpretation: Syntax - Almalki, Khalid Nasser; Pa, Mat Taib; Hussin, Mohamad (Al-Ḍād Journal, 2023)
The abundance of syntactic possibilities is part of the nature of the Arabic language, and it is one of the features of the Qur’anic text. It is replete with these possibilities and syntactic models. The weighting between these syntactic faces requires careful consideration, reflection, and analysis to reach the goal. The research is based on the role of grammar rules and meaning in weighing these syntactic faces, focusing on this phenomenon in the Holy Qur’an through the interpretation of al-Bayḍāwi. The research in general relied on the qualitative approach, and in particular on a complete extrapolation of the samples of the study from the linguistic structures in al-Zahrawayn (al-Baqarah & Āli ‘Imrān) with its multiple syntactic faces. Forty samples of syntactic faces were identified, which inspires the research to go beyond the theoretical side to the applied side, through which the study was able to stand on many aspects that help to weigh between the possible syntactic faces. The grammar rules stood next to the meaning to reach the goal. What the grammar rules agreed on with the meaning was the first in the preference, unless the meaning came out to a rhetorical purpose, then the grammar rules will be looked at to find an expression that agrees with the meaning. The study also revealed that if the grammar rules and the meaning agree in more than one inflectional aspect, then the most correct meaning is the uncomplicated meaning in it, so the apparent is the first unless the meaning calls for a rhetorical joke. The study also revealed that what has no condition takes precedence over others. Keywords: syntactic possibilities, weighting, interpretation of al-Bayḍāwi, linguistic structures, meaning